(untitled) (Mediscope, 2021)
Background: In a developing country like Bangladesh pregnancy induced hypertension is an important medical problem and a major cause of maternal and perinatal mortality and morbidity. Antihypertensive drugs are often used to lower blood pressure and also help in reducing maternal and fetal complications. Objective: To compare the efficacy and safety of labetalol and methyldopa in management of pregnancy induced hypertension. Methods: A total of 100 patients having newly onset hypertension during pregnancy were taken and divided randomly into two groups. Group A was given labetalol and group B methyldopa. In both groupsmean blood pressure was measured on 1stday as pretreatment and at 48th hour and 8th day as post-treatment measurement, total dose of each drug require per day and side effects were recorded.Reduction in blood pressure, doseand side effects were compared. Results: Labetalol treated group of patients showed significant fall in mean blood pressure from 1st day to 48th hour and 1st day to 8th day.In patients treated with labetalol mean blood pressure on 1st day was 123.9 ± 17.11 mmHg and was controlled to 100.03 ± 6.38 mmHg on 48th hour and 94.13 ± 4.3 mmHg on day 8, while in methyldopa treated group on 1st day was 121.23 ± 13.597 mmHg which was reduced to 105.8 ± 6.53 mmHg on 48th hour and 97.96 ± 4.11 mmHg on day 8.The mean drug dosage required to control BP in group A was 380 ± 259.5 mg and in group B was 1540 ± 503.45 mg. Group A had less side effects. Conclusion: Labetalol is safe more efficacious and quicker control of blood pressure withless maternal adverse effects and thus advantageous over methyldopa. Mediscope Vol. 8, No. 1: January 2021, Page 19-26